2014
DOI: 10.1016/j.socscimed.2014.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Are social organizational factors independently associated with a current bacterial sexually transmitted infection among urban adolescents and young adults?

Abstract: This study explored the relationship between the social organization of neighborhoods including informal social control and social cohesion and a current bacterial sexually transmitted infection (STI) among adolescents and young adults in one U.S. urban setting. Data for the current study were collected from April 2004 to April 2007 in a cross-sectional household study. The target population included English-speaking, sexually-active persons between the ages of 15 and 24 years who resided in 486 neighborhoods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Research on social capital has demonstrated protective associations with sexually transmitted infections among youth in ecological (state and community‐level) studies . Further, research conducted in the United States has noted protective associations of perceived social cohesion (most often measured as trust and closeness in a community) or social control (most often measured as expectations of reciprocity) with prevalence of sexually transmitted infections among youth and early sexual debut . There has been less exploration of these constructs in sub‐Saharan Africa, with little previous research on community social resources measured at the community level and its impact on adolescent health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on social capital has demonstrated protective associations with sexually transmitted infections among youth in ecological (state and community‐level) studies . Further, research conducted in the United States has noted protective associations of perceived social cohesion (most often measured as trust and closeness in a community) or social control (most often measured as expectations of reciprocity) with prevalence of sexually transmitted infections among youth and early sexual debut . There has been less exploration of these constructs in sub‐Saharan Africa, with little previous research on community social resources measured at the community level and its impact on adolescent health.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that the social environment, inclusive of the physical surround and cultural context in which social relationships occur and people interact , shape health and health behaviours . For example, studies of community well‐being or a sense of community connectedness, social capital and social cohesion have demonstrated protective effects on early sexual debut and rates of sexually transmitted infections in the US . Studies in multiple contexts have also found that women who perceive their environments to be cohesive or who engage in community groups have better sexual health outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…101 Other studies use more specific constructs, such as neighbourhood-level characteristics and HIV and STI. [102][103][104][105] For example, one study of sex partner meeting places showed that core transmitters were more likely to be found in venues with drug and sex 'market' activity. 102 Another study examining social support and cohesion among city neighbourhoods in the US found that informal social control at the neighbourhood level was protective for young women, but unrelated for young men; in contrast, individual social support was associated with a large increase in the odds of having an STI, but only for young men.…”
Section: Social Determinants Of Healthmentioning
confidence: 99%
“…102 Another study examining social support and cohesion among city neighbourhoods in the US found that informal social control at the neighbourhood level was protective for young women, but unrelated for young men; in contrast, individual social support was associated with a large increase in the odds of having an STI, but only for young men. 103 The authors of that study speculated that these counterintuitive findings may be based on the connections of young men with social support (e.g. to high-risk social networks in which norms supported risk, not protective behaviours).…”
Section: Social Determinants Of Healthmentioning
confidence: 99%